Penerapan Prinsip First to file Dalam Sengketa Merek Terkenal - Tanjung, Damar Ramadhanna; Njatrijani, Rinitami; Rahmanda, Bagus (Law, Development and Justice Review, 2023)
The “Superman” brand dispute between DC Comics and PT Marxing Fam Makmur was caused by the use of the first to file principle where the “Superman” brand owned by DC Comics could not be registered because the mark had already been registered by PT Marxing Fam Makmur. This study uses a normative juridical approach. The purpose of this study is to determine the legal protection for bad faith towards the well-known brand, namely "Superman" which is owned by DC Comics in accordance with Law No. 20 of 2016 concerning Marks and Geographical Indications and the application of the first to file principle in this trademark dispute. In the discussion, it is known that the legal protection for the "Superman" brand owned by DC Comics is in accordance with Law no. 20 of 2016 due to bad faith in the registration of the Superman brand owned by PT Marxing Fam Makmur. In this dispute the principle of first to file is used to determine who is entitled to the trademark "Superman".